Các hiệp định đối tác kinh tế - một con đường để phục hồi sức mạnh kinh tế của Nhật Bản - Trịnh, Lưu Ngọc (VNU Journal of Science: Legal Studies; Vol 20 No 2, 2004)
From the early 1990s, after the bursting of the economic bubble, Japanese economy has fallen in a long recession without a sign of sustainable recovery and, at the same time, its importance in the world and East Asia has been steadily declining since then. In context of regional and international changes unfavourable to Japan, in order to recover its declining competitiveness and to regain its regional leadership in East Asia, beside having carried out domestic basic economic structural reforms in direction of making its economy more free, decentralized, and less regulated, Japan is forced to open gradually its markets to the foreign factors and have more active contributions to the trade negotiations within the WTO framework, of which there are formation of the multilateral and bilateral free Economic Partnership Agreements (EPAs), first of all, with the regional neighboring economies. It may to say, the formation of EPAs with developing East Asian economies is a very effective way of achieving these objectives for Japan. It may be considerred as an outside pressure on Japanese economy to become more open, dynamic, and competitive. EPAs proposed by Japan should include not only trade and FDI liberalization and facilitation but also economic and technical assistance. Thus they are beyond free trade agreements (FTAs), which have been concluded by many countries in recent years. However, Japan will have to overcome various obstacles in forming EPAs. One of the major obstacles for Japan is to remove or reduce import protection in sensitive sectors, most notably agriculture and some service sectors such as finance and transportation.